PENGARUH DANA PIHAK KETIGA (DPK), NON PERFORMING FINANCING (NPF), FINANCING TO DEPOSIT RATIO (FDR) DAN OPERATIONAL EFFICIENCY RATIO (OER) TERHADAP PROFITABILITAS PADA BANK MUAMALAT - Putri, Seftia Talenta; Indrarini, Rachma (Jurnal Ekonomika dan Bisnis Islam, 2024)
The resilience of Bank Muamalat which has made Bank Muamalat survive until now can be assessed from its financial performance. Bank Muamalat's performance influences the profitability obtained by Bank Muamalat. This research intends to examine the influence of third party funds, non-performing financing, financing to deposit ratio, operational efficiency ratio on profitability at Bank Muamalat for the period 2013 - 2022. This research is quantitative in nature with an approach causal associative, and using non-probability sampling methods. Multiple Linear Regression data analysis technique using the SPSS application. The results of this research reveal that it is partially known that Third Party Funds do not have a significant effect on ROA, Non Performing Financing does not have a significant effect on ROA, Financing to Deposit Ratio has a significant positive effect on ROA, Operational Efficiency Ratio has a significant negative effect on ROA. third party funds, non-performing financing, financing to deposit ratio, operational efficiency ratio simultaneously influence profitability. The implication of the results of this research for Bank Muamalat is that it can maintain performance so that it can channel financing in accordance with existing regulations in order to obtain high profitability. It is hoped that future researchers will be able to add research periods and objects so that they can see other influences on profitability.